PERAN SEKOLAH DALAM PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS DI SDLB PGRI BANGOREJO BANYUWANGI - Harwanti Noviandari; Tian Fitriara Huda (Ilmu Psikologi Universitas Yudharta Pasuruan)
AbstractThis study aims to find out the school in developing the education of children with special needs in SDLB PGRI Bangorejo Banyuwangi City. The results of the study were used as a reflection of the school and the Banyuwangi Regency government on the education of children with special needs. This study uses a qualitative approach with a case study design that uses a phenomenological perspective. The selection of respondents using snow ball, where the sample in this study is the principal and teacher and resource persons related to this research are in SDLB PGRI Bangorejo Banyuwangi City. The results of this study indicate that the role of schools in the development of education for children with special needs is four (4) things, including: 1) the maximum use of BOS funds for the advancement of children's education, 2) coordinating with students to bring experts in the development of children's education and child independence, 3) always make new breakthroughs to find donors for the development of school facilities and infrastructure, 4) involve guardians of students in each school program